CITRAL HYDROGENATION OVER Pd-Fe/MgO - Linares F., T. (2012)
The aim of the study was the hydrogenation reaction on a catalyst Citral Pd-Fe/MgO and the reaction selectivity towards the different products obtained. Citral hydrogenation is performed in a batch reactor at 60° C with a solution of 2-propanol as solvent. The results show that the catalyst is Pd-Fe/MgO very active in the hydrogenation of the double bond adjacent to the carbonyl in the Citral and that catalyst activity sharply declines last 10 minutes of the reaction.